2019
DOI: 10.3389/fmicb.2019.00813
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect Against Toxoplasmosis in BALB/c Mice Vaccinated With Toxoplasma gondii Macrophage Migration Inhibitory Factor

Abstract: Toxoplasma gondii is an obligate intracellular parasite responsible for toxoplasmosis, which can cause severe disease in the fetus and immunocompromised individuals. Developing an effective vaccine is crucial to control this disease. Macrophage migration inhibitory factor (MIF) has gained substantial attention as a pivotal upstream cytokine to mediate innate and adaptive immune responses. Homologs of MIF have been discovered in many parasitic species, and one homolog of MIF has been isolated from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Three well-characterized antigens which play key roles in host-parasite interactions, were selected, including TgMIF, TgCDPK3, and Tg14-3-3 (16,19,20,23,44,45). Our study revealed that cocktail protein vaccine is a partial but effective method against acute or chronic toxoplasma infection, compared with vaccines only designed in single or two antigens (15,46). The study indicated that there is an increase in survival time and reduction of brain cysts in immunized mice, as well as enhanced humoral and cellular immune responses compared with the control mice groups or infected mice immunized with any two proteins.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Three well-characterized antigens which play key roles in host-parasite interactions, were selected, including TgMIF, TgCDPK3, and Tg14-3-3 (16,19,20,23,44,45). Our study revealed that cocktail protein vaccine is a partial but effective method against acute or chronic toxoplasma infection, compared with vaccines only designed in single or two antigens (15,46). The study indicated that there is an increase in survival time and reduction of brain cysts in immunized mice, as well as enhanced humoral and cellular immune responses compared with the control mice groups or infected mice immunized with any two proteins.…”
Section: Discussionmentioning
confidence: 93%
“…TgMIF is expressed in both tachyzoite and bradyzoite forms of the parasite ( 14 ). Our previous research revealed that TgMIF is a good vaccine candidate due to its excellent antigenic index and surface probability ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the vaccine still managed to confer partial protection in mice challenged with the ME49 strain via oxidative stress regulation involving iNOS expression [ 60 ]. T. gondii vaccines expressing the macrophage migration inhibitory factor (MIF) significantly protected immunized mice against acute and chronic toxoplasmosis upon a challenge infection with RH tachyzoites and PRU cysts [ 51 ].…”
Section: Vaccine Platforms Against T Gondiimentioning
confidence: 99%
“…A similar approach was used in studies in which vaccination with a DNA plasmid encoding Trichinella spiralis MIF or with a T. spiralis MIF fusion protein promoted Th1 responses and partial protection in infected mice [124,125]. Similarly, vaccination with Toxoplasma gondii MIF was shown to promote antibody and T cell responses, improve survival times and reduce brain cyst formation in infected mice [126]. The most impressive impact of vaccination against parasite MIF was shown in a study in which mice were immunized with a Plasmodium berghei MIF-encoding RNA vector prior to infection with blood or liver stage parasites.…”
Section: Targeting Mif For Therapeutic Applicationsmentioning
confidence: 99%